2014
DOI: 10.1002/2013jb010717
|View full text |Cite
|
Sign up to set email alerts
|

Current kinematics and dynamics of Africa and the East African Rift System

Abstract: Although the East African Rift System (EARS) is an archetype continental rift, the forces driving its evolution remain debated. Some contend buoyancy forces arising from gravitational potential energy (GPE) gradients within the lithosphere drive rifting. Others argue for a major role of the diverging mantle flow associated with the African Superplume. Here we quantify the forces driving present‐day continental rifting in East Africa by (1) solving the depth averaged 3‐D force balance equations for 3‐D deviator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 98 publications
(153 reference statements)
8
93
2
Order By: Relevance
“…The boundary forces at the plates' sides and bases and the buoyancy forces from lateral variations in gravitational potential energy are responsible for this motion and the resultant horizontal stress field (Craig et al, 2011;Stamps et al, 2014; Figure 2A). A normal faulting regime (vertical stress component (σ v ) greater than the two horizontal stress components: σ v = σ 1 > σ 2 > σ 3 ) dominates in the EARS, with a strike slip regime (vertical stress component is intermediate relative to the horizontal stress components: σ 1 > σ v > σ 3 ) more evident in some places (e.g., Asal-Ghoubbet Rift, Delvaux and Barth, 2009).…”
Section: Factors That Could Affect Stress and Strain In The Earsmentioning
confidence: 99%
“…The boundary forces at the plates' sides and bases and the buoyancy forces from lateral variations in gravitational potential energy are responsible for this motion and the resultant horizontal stress field (Craig et al, 2011;Stamps et al, 2014; Figure 2A). A normal faulting regime (vertical stress component (σ v ) greater than the two horizontal stress components: σ v = σ 1 > σ 2 > σ 3 ) dominates in the EARS, with a strike slip regime (vertical stress component is intermediate relative to the horizontal stress components: σ 1 > σ v > σ 3 ) more evident in some places (e.g., Asal-Ghoubbet Rift, Delvaux and Barth, 2009).…”
Section: Factors That Could Affect Stress and Strain In The Earsmentioning
confidence: 99%
“…A seaward propagation was recently revisited by Wiles et al (2014) as a probable cause for up to 31 km long and 18 km wide seafloor mounds observed northwest of the MozR. Other authors proposed that the western boundary of the Lwandle microplate traces along the eastern border of the MozR (Stamps et al 2008;Saria et al 2014;Stamps et al 2014), thus presenting another probable connection of neotectonic activity to a southward propagation of the EARS in the vicinity of the MozR.…”
Section: Post-sedimentary Magmatism At the Mozambique Ridgementioning
confidence: 99%
“…However, unlike the usual assumption, according to paleomagnetic data (Besse and Courtillot, 2003), Africa has a southward component of motion, supporting the shallow hotspot reference frame (Muluneh et al, 2014). Recently, Stamps et al (2014) found deviatoric stress resulting from GPE gradient is sufficient to drive Africa and Somalia plate separation and Quaternary to Recent deformation in East African Rift System (EARS).…”
Section: Introductionmentioning
confidence: 89%
“…However, Trampert et al (2004) questioned the existence of a deep mantle plume beneath Africa, arguing how the low-velocity of seismic waves could be related to denser Fe-rich lower mantle than to hot raising material. Stamps et al (2014) and Bird et al (2008) quantified the basal shear traction beneath Africa plate. These studies showed shear traction magnitudes varying by 1 order of magnitude.…”
Section: Comparison Of Side and Basal Torques In The Ethiopian Riftmentioning
confidence: 99%
See 1 more Smart Citation